2015
DOI: 10.1371/journal.pone.0133374
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Leucine, Zinc, and Chromium Supplements on Inflammatory Events of the Respiratory System in Type 2 Diabetic Rats

Abstract: Diabetes mellitus is a major cause of serious micro- and macrovascular diseases that affect nearly every system in the body, including the respiratory system. Non-enzymatic protein glycation due to hyperglycaemic stress has fundamental implications due to the large capillary network and amount of connective tissue in the lung. The current study was designed to determine whether leucine, zinc, and chromium supplementations influence the function and histological structure of the respiratory tract in a rat model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
2
20
0
4
Order By: Relevance
“…The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript' [262].…”
Section: Box 7 Examples Of Competing or Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript' [262].…”
Section: Box 7 Examples Of Competing or Conflicts Of Interestmentioning
confidence: 99%
“…‘This study was financially supported by the Tuberculosis and Lung Research Center of Tabriz University of Medical Sciences and the Research Council of University of Tabriz. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript’ [ 262 ].…”
Section: Recommended Setmentioning
confidence: 99%
“…The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript." [244] 3) "This work was supported by the salary paid to AEW. The funder had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript."…”
Section: ) "Support Was Provided By the Italian Ministry Of Health: mentioning
confidence: 99%
“…11 mg (14->70 years) Testosterone serum level (ng/ml) (Rey et al 2006) 1.00-3.00 (0-6 months) 2.68-5.60 (12-17 months) 0.10-0.32 (6-9 months) 2.80-8.00 adultZinc also plays a role in systemic glycemic control through its effects on insulin biosynthesis within pancreatic β-cells and probably by modulating the insulinemic effects on target tissues. Kolahian et al (2015) demonstrated that the supplementation of diabetic rats with leucine, zinc, and chromium, alone and in combination, was associated with significant improvements in the function and structure of respiratory system. The nutritional supplements enhance the enzymatic antioxidant activity of catalase, glutathione peroxidase, myeloperoxidase, and superoxide dismutase.…”
Section: Implications Of Zinc In Several Diseasesmentioning
confidence: 99%